2022
DOI: 10.48550/arxiv.2206.02273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constraining inputs to realistic kilonova simulations through comparison to observed r-process abundances

Abstract: Kilonovae, one source of electromagnetic emission associated with neutron star mergers, are powered by the decay of radioactive isotopes in the neutron-rich merger ejecta. Models for kilonova emission consistent with available modeling and the electromagnetic counterpart to GW170817 also predict characteristic abundance patterns, determined by the relative balance of different types of material in the outflow. Assuming the observed source is prototypical, this inferred abundance pattern in turn must match r -p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…They also showed that both optical and nearinfrared emissions are simultaneously reproduced by the ejecta with a medium Y e of 0.25. The recent Bayesian analysis by Ristic et al (2022) constrained a mass ratio of M w /M = 2.81 (the ratio of wind mass to dynamical ejecta mass) to reproduce the observed AT2017gfo kilonova light curves, while also being consistent with the observed r-process element abundance measured in the solar system.…”
Section: Comparison With Previous Studiessupporting
confidence: 55%
“…They also showed that both optical and nearinfrared emissions are simultaneously reproduced by the ejecta with a medium Y e of 0.25. The recent Bayesian analysis by Ristic et al (2022) constrained a mass ratio of M w /M = 2.81 (the ratio of wind mass to dynamical ejecta mass) to reproduce the observed AT2017gfo kilonova light curves, while also being consistent with the observed r-process element abundance measured in the solar system.…”
Section: Comparison With Previous Studiessupporting
confidence: 55%
“…Therefore, we generated a network with ∼800 species (in the following referred to as "full network"), including all relevant nuclei up to Ge and reactions, butnot including weak reactions. 9 This generated network is compared to the well-established reaction network WINNET (Winteler et al 2012), which was already used in previous publications (e.g., Korobkin et al 2012;Winteler et al 2012;Martin et al 2015;Eichler et al 2019;Bliss et al 2020;Reichert et al 2021;Ristic et al 2022). For this, we use three different typical explosive trajectories taken from the 2D_flsh model (see Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…7 Previous work found that solar-like abundances can be obtained by combining individual trajectories with both high initial Y e as well as low initial Y e (Zhu et al 2021). Our goal is not necessarily to obtain a solar-like final abundance pattern (we direct the reader to, for example, Ristic et al 2022, which addresses r-process universality), since we do not know if KN events produce a solar pattern. Rather we aim to sample a variety of trajectories containing material with a variety of neutron richness, whether from dynamical ejecta plus disk outflows or from multicomponent disk outflows.…”
Section: Model Set and Nucleosynthesismentioning
confidence: 99%